Multiple sclerosis : the guide to treatment and management - Polman, Chris (Demos, 2006)
The huge expansion of information available about MS, especially through the Internet, has put the individual with MS in a position to take increasing responsibility for her or his own care. There is thus a need for a comprehensive, readily accessible guide to the present therapeutic options, which will give the inquirer a balanced guide to the relative effectiveness of individual treatments. This book is designed to do just that. This bestselling title is a unique compendium of the most frequently used treatments for multiple sclerosis, an authoritative reference for all physicians, and a fact.